PERSEPSI KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN DI GREEN WHITE CAFÉ BOGOR - Benny Osta Nababan; Muhammad Fakhri Ramadhan (Institut Teknologi dan Bisnis Dewantara, 2020)
This study aims to determine the level of customer satisfaction with service quality at the Green White Café Bogor, then to determine the value of the consumer satisfaction index at the current Green White Café Bogor and the last is to determine the factors that must be improved so that customer satisfaction can be met. The population in this study were visitors to the Green White Café Bogor with a total sample of 100 respondents and was determined based on the Slovin formula. Data collection techniques were carried out using surveys and questionnaires, while for data analysis using the help of Microsoft Excel 2010 and SPSS version 22 software to test the validity test, reliability test, Service Quality (SQ), Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). ). The results showed that there were 12 service qualities that got a negative gap, 4 service quality that got a positive gap, and 1 that got no gap. Then for the value of the consumer satisfaction index at the Green White Café Bogor is currently 83.27%, which means that consumers feel quite satisfied but are not considered to be maximized overall, and in the importance performance analysis (IPA) analysis, there is one service attribute that must be a priority. main to be improved by café management in order to meet customer satisfaction.